The Effect of Malnutrition on the Recovery Rate of Lung Patients - Asyie, Maulana; Rosfadilla, Puspa (Formosa Journal of Sustainable Research, 2024)
Tuberculosis (TB) is a direct infectious disease caused by the Mycobacterium tuberculosis bacteria. This disease generally attacks the lungs (90%) and can be transmitted through the air. Clinical symptoms of TB include coughing up phlegm, fever, weight loss and malaise. Risk factors for TB include: HIV positive, smoking, alcohol, age <5 years and elderly. TB diagnosis is made through bacteriological, radiological and clinical examinations. TB treatment uses a combination of Anti-Tuberculosis Drugs (OAT) consisting of Rifampicin, Isoniazid, Pyrazinamide and Ethambutol for 6 months. The goal of treatment is to cure patients, prevent death, disability and transmission. Pulmonary tuberculosis (TB) is closely related to nutritional status. Malnutrition increases the risk of pulmonary TB and worsens its prognosis. Pulmonary TB also causes malnutrition because the disease process affects the body's immune system. Improving nutritional status through consumption of nutritious foods, especially protein, vitamins and minerals, can increase the body's immune system and break the cycle of TB transmission